Javanese language shift in the coastal area of special region of Yogyakarta province / Dwi Atmawati - Atmawati, Dwi (Universiti Teknologi MARA, 2020)
Indonesia has one national language, namely Indonesian and 718 local languages. One of the local languages in Indonesia is Javanese. Javanese has levels, namely Javanese krama and Javanese ngoko. Krama Javanese is usually used for the purpose of respect or politeness. Ngoko Javanese is usually used to communicate with people of the same age. The data were collected by means of observation, surveys, interviews, and distributing questionnaires to respondents. This data was primary data. Respondents were selected by purposive sampling technique. The procedures for analyzing data were inputting data, grouping question items, calculating the composition of respondents, compiling and describing the index. The data were processed using the SPSS program and then analyzed qualitatively and quantitatively. The theory used was the theory of language shift. The results of this study indicated that in the DIY coastal area there was a shift in the use of Javanese. In the past, Javanese was used to communicate with the family and in daily conversations with fellow Javanese people, now some of its speakers have switched to using Indonesian. Speakers of children and adolescents tended to be less able to speak Javanese, both ngoko and krama. The vitality of the Javanese language in the DIY coastal area based on the calculation of the indicator index was 0.73. The index value indicates that Javanese in the DIY coastal area was in the index number 0.61-0.80 or in a stable but threatened position.